2016
DOI: 10.1093/bja/aew071
|View full text |Cite
|
Sign up to set email alerts
|

The role of peripheral afferents in persistent inguinal postherniorrhaphy pain: a randomized, double-blind, placebo-controlled, crossover trial of ultrasound-guided tender point blockade

Abstract: NCT02065219.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“… 34 In a study, it was tested to use injections at tender points, meaning that the point of injection was tailored to each patient depending on where in the groin the pain was. 35 The study demonstrated some effect indicating that the peripheral nerves were involved in the chronic pain, but unfortunately, the effect did not last. 35 A recent study on injections with a mix of lidocaine, corticosteroids, and hyaluronic acid has investigated the use of up to three repeated injections over 6 weeks in order to treat chronic pain compared with surgical neurectomy.…”
Section: Injectionsmentioning
confidence: 92%
See 1 more Smart Citation
“… 34 In a study, it was tested to use injections at tender points, meaning that the point of injection was tailored to each patient depending on where in the groin the pain was. 35 The study demonstrated some effect indicating that the peripheral nerves were involved in the chronic pain, but unfortunately, the effect did not last. 35 A recent study on injections with a mix of lidocaine, corticosteroids, and hyaluronic acid has investigated the use of up to three repeated injections over 6 weeks in order to treat chronic pain compared with surgical neurectomy.…”
Section: Injectionsmentioning
confidence: 92%
“… 35 The study demonstrated some effect indicating that the peripheral nerves were involved in the chronic pain, but unfortunately, the effect did not last. 35 A recent study on injections with a mix of lidocaine, corticosteroids, and hyaluronic acid has investigated the use of up to three repeated injections over 6 weeks in order to treat chronic pain compared with surgical neurectomy. The study demonstrated a 22% success rate, which was lower than the 71% success rate for the neurectomy group.…”
Section: Injectionsmentioning
confidence: 92%
“…First , confounding is likely, due to lack of blinding and randomization with regard to re-surgical or pharmacotherapy. As an example, baseline Q0 maximal pain intensity was significantly higher in the re-surgery group compared to the pharmacotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 2016, it was found that patients who developed CPOP after breast cancer surgery were significantly more hyperalgesic to generalized pressure both 5 days after surgery and from 15 days to 12 months compared to patients who did not develop pain, suggesting that persistent central sensitization is an important process in CPOP development 46 . Also in 2016, a trial of 14 patients with CPOP, following inguinal hernia surgery, found that a tender point block with bupivacaine provided analgesia and reduced evoked pain responses, supporting the role of peripheral afferents in the maintenance of pain 47 . In addition to central sensitization from the surgical insult, which is maintained by peripheral input and peripheral sensitization of the primary nociceptors in the surgical field, other (non-mutually exclusive) potentially causal mechanisms for CPOP have been suggested 48 .…”
Section: Neural-based Mechanismsmentioning
confidence: 97%